Rapid prototyping of microfluidic devices by SL 3D printing and their biocompatibility study for cell culturing. (2019) - Moreno-Rivas, O.; Hernández-Velázquez, D.; Piazza, V.; Marquez, S.
Abstract: In this work, we demonstrate the feasibility of creating biocompatible microfluidic devices using stereolithography (SL) 3D printing as a simple and low-cost methodology compared to conventional soft-lithography carried on at cleanroom facilities. SL printing has gained much interest for rapid prototyping of designs in the fields of jewelry, dentistry and materials engineering. Therefore, we exploit this potential in microfluidics for creating biocompatible devices using three different types of photocurable resins. The resins are: Clear standard, High Temp and Dental LT (Formlabs, USA). Special attention is dedicated to investigate the minimum feature size (MFS), roughness and design-orientation dependence of SL printed microchannels. To the best of our knowledge, cytotoxicity research of UV curable resins for SL printing has been done in literature for short incubation times (<1 h). Therefore, we have also qualitatively and quantitatively studied the biocompatibility of the three resins during a 5 day experiment by culturing HeLa cells. By following a simple surface functionalization strategy using poly-D-Lysine, cell adhesion to SL printed substrates is improved. This approach opens up a pathway for fabricating low-cost, portable and biocompatible microfluidic devices subject to the imagination of the designer to create new biocompatible materials for biosensing applications.